2023
DOI: 10.1002/adfm.202215027
|View full text |Cite
|
Sign up to set email alerts
|

Dilute Aqueous Hybrid Electrolyte with Regulated Core‐Shell‐Solvation Structure Endows Safe and Low‐Cost Potassium‐Ion Energy Storage Devices

Abstract: High‐concentration “water‐in‐salt” (WIS) electrolytes with the wider electrochemical stability window (ESW) can give rise to safe, non‐flammable, and high‐energy aqueous potassium‐ion energy storage devices, thus highlighting the prospect for applications in grid‐scale energy storage. However, WIS electrolytes usually depend on highly concentrated salts, leading to serious concerns about cost and sustainability. Here, an aqueous low‐concentration‐based potassium‐ion hybrid electrolyte is demonstrated with the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(7 citation statements)
references
References 50 publications
(80 reference statements)
0
7
0
Order By: Relevance
“…The viscosity and conductivity of the electrolyte were compared, (Figure 1b and 1c) and it was observed that the addition of additives resulted in a decrease in ion conductivity. Aqueous solutions are known to have a higher ion conductivity than other solutions, and the presence of additional solvent molecules may be obstacles on the transmission path, [21] thereby interfering with the rapid transmission of ions. The viscosity test results showed that the presence of DMF did not significantly change the viscosity of the solution, possibly due to its strong solvating ability and water‐miscibility.…”
Section: Resultsmentioning
confidence: 99%
“…The viscosity and conductivity of the electrolyte were compared, (Figure 1b and 1c) and it was observed that the addition of additives resulted in a decrease in ion conductivity. Aqueous solutions are known to have a higher ion conductivity than other solutions, and the presence of additional solvent molecules may be obstacles on the transmission path, [21] thereby interfering with the rapid transmission of ions. The viscosity test results showed that the presence of DMF did not significantly change the viscosity of the solution, possibly due to its strong solvating ability and water‐miscibility.…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, most of the organic-based additives can undermine the safety and environmental friendliness of aqueous batteries. [47] In this context, a new dilute aqueous hybrid electrolyte was developed by Chen et al [47] It has a core-shell solventized structure consisting of a low salt concentration (1.6 M potassium trifluoromethanesulfonate) and broke the interaction between water molecules by using a nonprotonic solvent (trimethyl phosphate) with a wide electrochemical stability window (3.4 V) as well as high safety (Figure 5j). The PIB consisting of a K 1.5 Mn 0.61 Fe 0.39 [Fe-(CN) 6 ] 0.77 • H 2 O cathode and this dilute water mixed electrolyte could work well at 0.2 to 4 C and provided a high energy density of 66.5 Wh g À 1 .…”
Section: Co-precipitation Methodsmentioning
confidence: 99%
“…Copyright (2023), with permission from Elsevier Inc. (j) Electrochemical stability window for various electrolytes and enlarged views of the regions corresponding to the potentials for hydrogen and oxygen evolutions, respectively. Reproduced from ref [47]. Copyright (2023), with permission from Wiley-VCH GmbH.…”
mentioning
confidence: 99%
“…Importantly, the ionic conductivity of aqueous electrolytes is two orders of magnitude higher than that of non-aqueous electrolytes [ 6 8 ]. So far, various lithium-rich alkali metal cations [ 9 12 ] (such as Na + and K + ) [ 13 ] and multivalent charges [ 14 18 ] (such as Mg 2+ , Al 3+ , and Zn 2+ ) have been developed. Redox reactions in multivalent ionic systems, which involve multiple electrons, can potentially achieve higher energy densities [ 19 21 ].…”
Section: Introductionmentioning
confidence: 99%